Kontribusi Ekonomi Syariah Terhadap Pembangunan Berkelanjutan Di Indonesia: Perspektif 2023-2024 - Citra Anggela; Farah Wahidah; Novi Atika Putri (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
The Islamic economy has grown rapidly in Indonesia in recent years, offering an alternative financial system that is aligned with Islamic principles. With a focus on justice, ethics, and sustainability, the Islamic economy has the potential to make a significant contribution to sustainable development in Indonesia. This paper explores the contribution of the Islamic economy to the achievement of the Sustainable Development Goals (SDGs) in Indonesia in the 2023-2024 period. In-depth analysis was conducted on the Islamic financial sector, including banking, capital markets, and non-bank financial institutions, as well as halal industries such as food, tourism, and fashion. The results show that the Islamic economy can support the achievement of SDGs through responsible investment practices, inclusive finance, poverty alleviation, and sustainable resource management. However, challenges such as inadequate regulation, low Islamic financial literacy, and lack of synergy among stakeholders need to be overcome to maximize the contribution of the Islamic economy to sustainable development in Indonesia.